Biologia reprodutiva de surubins do Iguaçu, Steindachneridion melanodermatum, em condições de cativeiro - Tessaro, Lucelia [UNESP] (2015)
Understand events and reproductive dynamics is essential for the appropriate management and control of reproductive function in captivity. The species, ―surubim do Iguaçu‖ is include in Iguaçu river reintroduction programs and offspring's were obtain by induce spawning, but reproductive biology aspects, as first maturation age and reproductive season are lower explored or no available. The research was realized to provide information about surubim's reproductive development, in captive conditions. Were evaluated juvenile individuals, with one year old, every month due 24 and 36 months, to male and female, respectively. Were evaluated gonad developments, cell modifications and steroids fluctuations (estradiol and testosterone), during all experimental time. The fish showed gradative growth and weight gain. Female present slow sexual development and stay in immature status after 48 months (4 years age). Cellular modifications and steroids elevation levels were verified, and peaked of steroids occur in same time of male peaked. Male showed reproductive cycle with two years old and all reproductive phases of were observed. The gonadal development with to cellular changes and steroids fluctuation indicates the breeding season the males in the months from September to November (spring)